The Implication of Recognition Principle in the Administraton of Village Governance - Endang Retnowati; Edi Krisharyanto; Noor Trihastuti (NOTARIIL Jurnal Kenotariatan, 2018)
This study aims to analyze the implications of the existence of the principle of recognition to the administration of village governance. The method used is normative method with juridical, statute, and doctrinal approaches. The principle of recognition brings the existence of the village to play an independent role in the administration of village governance and the affairs of the village while increasing the participation of the village community in realizing good governance. This principle of recognition is also an alternative in exploring the origin of the village in question, especially for villages that are beginning to forget their origins. Notwithstanding, basically the principle of recognition is recognizable as long as it is still alive and applies in the village concerned.